Review of the Palaeozoic Stratigraphy of the Langkawi Islands, Malaysia - Chai Peng Lee (Berita Sedimentologi, 2013)
The Langkawi group of 99 islands off the northwest coast of Malaysian Peninsula is located some 30 km off the coast of Perlis and 112 km north of Penang. These islands are a paradise for geologists, including some of the best and most interesting exposures of Palaeozoic sedimentary rocks in Malaysia, ranging in age from Cambrian to Permian. These consist of both clastics and carbonates, deposited within a range of depositional and palaeoclimatic conditions ranging from shallow marine shoreface to turbidites with dropstones. In addition, these sedimentary rocks had been intruded by younger Mesozoic granites with considerable contact metamorphic effects.Since the initial publication of the Geological Map of Langkawi and the subsequent Geology and Mineral Resources Memoir 17 on the States of Perlis, North Kedah and the Langkawi Islands, both by Jones (1966, 1981) many more recent studies had been carried out. These studies were particularly facilitated by the creation of new outcrops due to numerous recent development projects on the islands. A helpful compilation of published and unpublished geological researches on Langkawi was compiled by Sarman et al. (1997).The spectacular geological heritage of the islands heralded the formation of the Langkawi Geoforestpark by the Kedah State Government, Malaysia in May 2006 to preserve and display its unique geological features. The Geoforestpark was endorsed by the United Nations Educational, Scientific and Cultural Organization (UNESCO) under the Global Network of National Geoparks in June 2007 (Leman et al., 2007).